2020
DOI: 10.3390/su12156008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Olive Oil Tourism as a Type of Special Interest Tourism: An Analysis from the Tourist Experience Perspective

Abstract: Olive oil tourism is an emerging activity that is sparking a growing interest among tourists seeking to partake in this experience and the self-fulfilment it offers. An ever-greater number of olive oil mills are diversifying their businesses to incorporate this type of tourism. In this article, olive oil tourism is characterized as a type of special interest tourism (SIT), under a demand-side approach. Based on quantitative research carried out with olive oil tourists, which examined the aspects of the destina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Considering Spain, Italy, and Croatia, the three Mediterranean countries upon which this research is based due to their results in terms of top-quality production, it is observed that the oleotourism activities offered are strongly related to the enjoyment of experiences in a traditional local environment. This is related to studies that classify oleotourism as a type of special interest tourism, characterizing it with indicators such as sustainability, experience, the promotion of local culture, and the image of prestige/status (Parrilla-González et al, 2020 [16]; Pulido-Fernández et al, 2019 [15]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering Spain, Italy, and Croatia, the three Mediterranean countries upon which this research is based due to their results in terms of top-quality production, it is observed that the oleotourism activities offered are strongly related to the enjoyment of experiences in a traditional local environment. This is related to studies that classify oleotourism as a type of special interest tourism, characterizing it with indicators such as sustainability, experience, the promotion of local culture, and the image of prestige/status (Parrilla-González et al, 2020 [16]; Pulido-Fernández et al, 2019 [15]).…”
Section: Discussionmentioning
confidence: 99%
“…Proactive planning and identifying strategic objectives in the case of each above-mentioned country are the key steps to future oleotourism development. It is evident that a certain group of stakeholders within all three countries is increasingly diversifying (Parrilla-González et al, 2020) [16] its core business and bonding it to tourism (Pulido-Fernández et al, 2019) [15]. This enables the system to be economically sustainable.…”
Section: Discussionmentioning
confidence: 99%
“…The bivariate analysis also shows that foreign tourists are more satisfied; therefore, this work could be used by entrepreneurs to advertise oil tourism in international markets and increase the demand of oil tourists because they are the ones who most value this market niche. However, the dimensions of experience and sustainability analyzed in the work of Parrilla-González et al, [ 7 ] in the province of Jaen would have to be considered to transform Córdoba’s oleotourism into not only gastronomic tourism but also experiential tourism, given the uniqueness of the oil in the Mediterranean Basin.…”
Section: Discussionmentioning
confidence: 99%
“…The use in the museum of artefacts and objects that have been preserved by society positively influences the degree of museumization of olive oil mills. (Parrilla-González et al 2020). Such experiences are based on tourism, especially cultural tourism (Herrero 2011) and what is known as Special Interest Tourism (SIT).…”
Section: Theorymentioning
confidence: 99%
“…Such experiences are based on tourism, especially cultural tourism (Herrero 2011) and what is known as Special Interest Tourism (SIT). In the case of olive oil tourism, these may include activities such as visiting an olive grove; taking part in olive harvesting; visiting olive oil mills, interpretation centres or museums (Parrilla-González et al 2020). There is another type related to industrial heritage tourism, which expands the cultural experience available to tourists.…”
Section: Theorymentioning
confidence: 99%